Partial Clinical Remission of Type 1 Diabetes in Swedish Children : A Longitudinal Study from the Swedish National Quality Register (SWEDIABKIDS) and the Better Diabetes Diagnosis (BDD) Study - Fureman, Anna Lena; Bladh, Marie; Carlsson, Annelie ; 0000-0002-5608-3437; Forsander, Gun; Lilja, Mikael; Ludvigsson, Johnny; Samuelsson, Ulf; Särnblad, Stefan; Lind, Torbjörn (Diabetes Technology and Therapeutics, 2024)
Aims/Hypotheses: To investigate the frequency and characteristics of partial remission in Swedish children with type 1 diabetes and whether the insulin delivery method, that is, continuous subcutaneous insulin infusion (CSII) or multiple daily injections (MDIs), affects incidence and duration of this period, 2007-2011. Factors that increase the proportion of subjects who enter partial remission and extend this period can improve long-term metabolic control and reduce the risk of severe hypoglycemia, improve quality of life, and, in the long run, reduce late complications. Methods: Longitudinal data from 2007 to 2020 were extracted from the Swedish National Quality Register (SWEDIABKIDS) with all reported newly diagnosed children. Data on C-peptide from the participants in the Better Diabetes Diagnosis study from 2007 to 2010 were used. The definition of partial remission was insulin dose-adjusted HbA1c: HbA1c (%) + [4 · total daily insulin dose (U/kg/day)] £9. Results: Of the 3887 patients, 56% were boys. More boys than girls were in partial remission throughout the follow-up period until 24 months after diabetes onset. Fewer children 0-6 years old had partial remission at 3 and 12 months but not at 24 months compared with older age-groups. A larger proportion of patients using CSII at 12 and 24 months remained in partial remission compared with those with MDI (37% vs. 33%, P = 0.02 and 31% vs. 27%, P = 0.01, respectively). The level of C-peptide was higher in the group with partial remission and mean HbA1c was lower (both P < 0.001). Partial remission at 12 months after diabetes onset was associated with CSII (odds ratio [OR]: 1.39, confidence interval [CI]:1.13, 1.71), shorter diabetes duration (OR: 0.80, CI: 0.76, 0.84), and male sex (OR: 1.23, CI: 1.04, 1.46). Conclusions/Interpretation: Insulin through MDI, longer duration of diabetes, and female sex were associated with lower frequency of partial remission. Use of CSII seems to contribute to longer partial remission among Swedish children with type 1 diabetes.
Keywords: C-peptide; continuous subcutaneous insulin infusion; HbA1c; multiple daily injection; partial clinical remission